Student Analysis Of Differences Perceptions On Professionalism Of Lecturer In Palembang - Delta Khairunnisa, Indri Ariyanti, Nita Novita, M. Aris Ganiardi (Jurnal Manajemen, 2019)
The research entitled Student Analysis of Differences Perceptions on Professionalism of Lecturer in Palembang. The purpose of this research is to know the perception of student to professionalism of lecturer in vocational and academic education. Data collection was done by distributing questionnaires using 5 Likert scales. Sampling using purposive sampling. Analytical technique used is Structural Equation Model (SEM). The results obtained in this study is there are significant student perception to professionalism of the lecturers, in terms of knowledge, skill and personality. The implication of this research is to be effective, lecturers need a combination of professional knowledge and specialized skills as well as their own personal qualities and experiences.